Perubahan kadar kolesterol total dan trigliserida pada kelinci New Zealand white yang diberi ekstrak beras hitam (Oriza sativa L.) - Glory, Lastry; Kawengian, Shirley E.; Mayulu, Nelly (Universitas Sam Ratulangi, 2016)
Abstract: High cholesterol levels in blood can lead to various diseases, including coronary heart disease. Black rice (Oryza sativa L.) contains more anthocyanin in layers of alueron than in white rice. Cardioprotective effect of rice has been emerged since several decades ago. This was a true experimental study with a pre-posttest control group design. Samples were New Zealand White male rabbits aged 3 months. Group 1 was fed standard meal; group 2 was fed with high-fat diet; group 3 was fed with high-fat diet plus black rice extract; and group 4 were fed with high-fat diet plus atorvastatin. Data were analyzed and presented descriptively. The results showed that total cholesterol and triglyceride levels in the group fed with black rice extract decreased by 5 mg/dl and 4 mg/dl respectively. Decreased total cholesterol and triglyceride levels were also found in the group fed with standard meal and the group given atorvastatin. Meanwhile, the group fed with high-fat diet showed increased levels of total cholesterol and triglyceride high enough. Conclusion: There were decreased levels of total cholesterol and triglycerides in rabbits fed with black rice extract. Keywords: black rice extract, total cholesterol, triglycerides.Â Abstrak: Kadar kolesterol yang tinggi dalam darah dapat memicu berbagai macam penyakit, diantaranya penyakit jantung koroner. Beras hitam (Oryza sativa L.) mengandung lebih banyak antosianin dalam lapisan alueronnya dibandingkan beras putih. Efek kardioprotektif dari beras telah dikemukakan sejak beberapa dekade yang lalu. Jenis penelitian ini true experimental dengan pre test post test control grup design. Sampel ialah kelinci New Zealand White jantan berusia 3 bulan. Kelompok perlakuan 1 diberi pakan standar; kelompok 2 diberi diet tinggi lemak; kelompok 3 diberi diet tinggi lemak dan ekstrak beras hitam dan kelompok 4 diberi diet tinggi lemak dan atorvastatin. Data dianalisis dan disajikan secara deskriptif. Hasil penelitian memperlihatkan kadar kolesterol total dan trigliserida pada kelompok yang diberi ekstrak beras hitam mengalami penurunan masing-masing sebesar 5 mg/dl dan 4 mg/dl. Penurunan kadar kolesterol dan trigliserida juga terdapat pada kelompok yang diberi pakan standar dan kelompok yang diberi atorvastatin. Pada kelompok yang diberi diet tinggi lemak terjadi peningkatan kadar kolesterol total dan trigliserida yang cukup besar. Simpulan: Terjadi penurunan kadar kolesterol total dan trigliserida pada kelinci yang diberi ekstrak beras hitam.Kata kunci: ekstrak beras hitam, kolesterol total, trigliserid.